(untitled) (Research, Society and Development, 2020)
The state of conservation and the quality of the built environment influences the health and quality of life of its users, especially in teaching environments. In order for students to develop cognitive skills, it is necessary that the building environments do not hinder the teaching-learning process, as in the occurrence of unhealthy places that present pathologies. The school chosen for this study has elementary school students aged between 4 and 6 years, with susceptibility to allergies and respiratory problems, implying the need for periodic evaluation of the conservation status of the building. Therefore, this work aims to analyze and propose solutions for the pathologies observed in the teaching unit in the municipality of Juazeiro do Norte from a methodology based on a technical report from surveys with visual inspections, tactile, plaster seal tests and evaluation of the thickness of the cracks. In view of the data obtained, the main pathologies, their possible causes, were identify. Solutions were subsequently proposed and the existing level of risk identified. It was evidence that the main pathological manifestations were observe in the walls, floors and facades, with emphasis on the cracks, in addition to displacement of coating, stains and infiltrations.